2004
DOI: 10.1016/j.ymthe.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Autologous Tumor Vaccines Transduced with the GM-CSF Gene in Four Patients with Stage IV Renal Cell Cancer in Japan: Clinical and Immunological Findings

Abstract: We produced lethally irradiated retrovirally GM-CSF-transduced autologous renal tumor cell vaccines (GVAX) from six Japanese patients with stage IV renal cell cancer (RCC). Four patients received GVAX ranging from 1.4 x 10(8) to 3.7 x 10(8) cells on 6-17 occasions. Throughout a total of 48 vaccinations, there were no severe adverse events. After vaccination, DTH skin tests became positive to autologous RCC (auto-RCC) in all patients. The vaccination sites showed significant infiltration by CD4(+) T cells, eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…27,[52][53][54][55] Interestingly, many cell vaccination studies for cancer therapy have focused on using GM-CSF as the preferred cytokine of choice based on initial data that identified it to be the best cytokine. [56][57][58][59][60] However, in the initial comparison study IL-12 was not tested, 56 and at least one recent study suggests that very high doses of GM-CSF can result in adverse immunosuppressive effects. 61 Taken together, the above-cited studies suggest that IL-12 might be the better cytokine for inducing a more robust antitumoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…27,[52][53][54][55] Interestingly, many cell vaccination studies for cancer therapy have focused on using GM-CSF as the preferred cytokine of choice based on initial data that identified it to be the best cytokine. [56][57][58][59][60] However, in the initial comparison study IL-12 was not tested, 56 and at least one recent study suggests that very high doses of GM-CSF can result in adverse immunosuppressive effects. 61 Taken together, the above-cited studies suggest that IL-12 might be the better cytokine for inducing a more robust antitumoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent clinical trials of patients with diverse solid cancers, cancer immunotherapy such as therapeutic vaccination with granulocyte macrophage colony-stimulating factor (GM-CSF) gene-transduced tumor vaccines (GVAX), as well as sipuleucel-T (Provenge; Dendreon), the first FDA-approved GM-CSF-based therapeutic dendritic cell (DC) vaccine for prostate cancer, induced antitumor immune responses with tolerability (1)(2)(3). However, the efficacy of this therapy alone is not satisfactory, raising an urgent need to improve the antitumor effect of GVAX.…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous immunostimulatory cytokines used for tumor vaccines, GM-CSF has been the most intensively investigated and widely studied for use in clinical cancer vaccine trials. [1][2][3] Immunization with irradiated tumor cells engineered to secrete GM-CSF stimulates potent tumor-associated antigen (TAA)-specific antitumor immunity in preclinical 4,5 and clinical settings, including solid tumors and acute myeloid leukemia. 6,7 We have recently shown that the GM-CSF gene-transduced murine monocytic leukemia of WEHI3B cells lose their tumorigenicity when subcutaneously administered into wild-type (WT) BALB/c mice.…”
mentioning
confidence: 99%